(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2023)
Nuclear Medicine (NM) is a medical specialty that, through non-invasive methods, uses radioactive materials for diagnostic and therapeutic purposes. According to Standard NN 3.05 of the Brazilian National Nuclear Energy Commission (CNEN), a Nuclear Medicine System (NMS) must be composed of, at least, a Holder, a Nuclear Physician, a Radiation Protection Supervisor and higher and mid-level professionals, duly qualified for the performance of their duties, which may be exercised, in this case, by a radiology technician. Thus, in 2009, the National Council of Radiology Technicians (CONTER) granted a period of 5 (five) years for radiology technicians who work in the NM and Radiotherapy specialties to specialize in their areas of expertise, a period that was extended for another 5 (five) years. In this sense, this paper aims to carry out a survey of the Technical Specialization courses in NM offered in Brazil, considering that almost 10 years have passed since the CONTER Resolution No. 17, of 2014, verifying aspects such as structure and workload, based on the requirements of the Ministry of Education (MEC), in order to suggest a core curriculum for courses in NM. It was found that, with the legal requirement of this training, these courses began to be offered, but in a reduced number and only in some regions of Brazil, despite the existence of courses in the distance modality. It is understood, therefore, that an expansion of courses in the area is necessary, in view of the relevance of the service for NM.